Design and Application of Genetic Algorithm Based on Signal Game and Newsboy Model for Optimizing Supply Chain - Yue Zhao; Yang Shen; Jiaqi Yan (Discrete Dynamics in Nature and Society)
Reasonable communication and cooperation between enterprises are helpful for the efficient operation of a supply chain. To explore the maximum utility of an entire supply chain, we propose a supplier-manufacturer-seller supply-chain game decision-making model. We use the model as the fitness function of a genetic algorithm that calculates the optimal solution and optimizes the total utility parameters. We analyze the theoretical and practical properties of the supply-chain optimization process and implement it in MATLAB, which provides quantitative support and useful references for making business decisions and optimally managing a supply chain.